An Implementation Of The Dual Local Decomposition Method - Coad, Leonard A.; Panne, Cornelis Van De (INFOR. Information systems and operational research, 1991)
The paper deals with a method for solving a linear programming problem with a primal block-angular structure. Any basic solution of such a problem can be decomposed into a principal problem and the remaining independent subproblems. A dual method working on an infeasible principal problem interacts with all the remaining independent subproblems to yield an optimal solution to the entire problem. Some implementation results for primally and dually feasible initial solutions using randomly generated problems are given.